Exploring Indoor Environmental Comfort in Pagoh Residential College (KKKP) - Kamal, Nur Sabrina Dayana; Anak Alih, Angelina Jolie; Mohd Shah, Nurul Syafiqah; Abd Kadir, Aslila (Multidisciplinary Applied Research and Innovation, 2025)
Indoor environmental quality (IEQ) refers to the overall quality of the indoor environment and its impact on occupant health, comfort, and productivity. In recent years, there has been a growing recognition of the importance of IEQ in buildings, as research has shown that poor indoor environments can lead to various health problems, including respiratory issues, and allergies. The aim of this study is evaluating the Indoor Environmental Quality (IEQ) in the student residential college at UTHM.  The measurement time taken for each parameter is different but still concentrated at night. The data was obtained with the standard used in Malaysia. For thermal comfort, our country has used ASHRAE Standards. For lighting comfort and sound comfort parameters, it has used Standard MS1525:2014 and standard from MESTECC to refer to the comfort level in a place or a building. One key aspect of IEQ is air quality, a indoor air pollution can be a major concern in buildings that are poorly ventilated or have sources of contamination such as mould or volatile organic compounds (VOCs). Poor indoor air quality can also affect cognitive function and productivity. Moreover, the key aspect of IEQ is thermal comfort, as the temperature and humidity levels can significantly impact occupant comfort and well-being. Buildings that are too hot or too cold can lead to discomfort, decreased productivity, and health problems. Meanwhile, lighting as natural and artificial lighting can affect both physical and mental health. Natural lighting has been shown to improve mood, productivity, and overall well-being, while poor lighting can lead to eyestrain, headaches and fatigue. Lastly, sound comfort plays a key role in IEQ as excessive noise levels can lead to stress, and fatigue. Buildings that are poorly insulated or located near noisy sources can create a disruptive environment that negatively impacts an occupant's well-being.